Studies on the diversity and distribution of marine ichthyoparasites in Southern Africa - Nunkoo, Muhammad Azher Irfan (Department of Biological Sciences, 2020)
Parasites are a vital component of ecosystems. However, their contribution to the functioning and structuring of ecosystems has historically been overlooked worldwide. In South Africa, marine ichthyoparasitology has a long history but research has largely been confined to taxonomic studies and the literature pertaining to marine ichthyoparasites is highly fragmented. This situation makes it difficult to gauge advances in marine parasitology, identify knowledge gaps and hampers our understanding of their ecological roles in the marine environments of Southern Africa as well as their use as tools in fisheries science. This thesis aims to explore the diversity of metazoan marine ichthyoparasites reported from Southern African waters and to examine their inter- and intraspecific distribution in marine fishes. A review of two centuries of parasitological literature, 1818 to 2017, revealed that 378 marine ichthyoparasites have been recorded off South Africa and included taxa from six phyla: Acanthocephala (12), Annelida (6), Arthropoda (210), Cnidaria (11), Nematoda (6) and Platyhelminthes (133). The parasites formed 723 unique host-parasite pairs with 269 host taxa spread across the classes Actinopterygii (186), Elasmobranchii (80), Holocephalii (2) and Myxini (1). Host species with the most diverse parasite assemblages were species of commercial significance, namely Thyrsites atun (20) followed by Merluccius capensis (17). The dominance of arthropods and platyhelminthes, which together accounted for 90.7% of the parasites found, reflects the interest and expertise of local and foreign researchers who have worked in South Africa. The parasite assemblage of selected commercially significant fish species was used to assess the degree of interspecific similarity in parasite community structure and identify the drivers of ichthyoparasite community assembly in the Southern Benguela. The examination of 554 specimens comprising six fish species (Brama brama, Chelon richardsonii, Merluccius capensis, Merluccius paradoxus, Sardinops sagax and Thyrsites atun) caught off the South African west coast revealed that they hosted 41 metazoan parasite taxa. These included 10 new host records and five new geographic records. Thyrsites atun and C. richardsonii had the most speciose component communities being infected by 17 and 14 taxa respectively. Multivariate analyses revealed that host habitat and identity in conjunction with the host specificity of ectoparasites influenced the community structure of ectoparasitic assemblages. Larval endoparasite community structure, on the other hand, differed between inshore and offshore habitats. Within the offshore habitat, further variation in endoparasite communities were driven by the host species‘ position in the food web, its trophic ecology and its vulnerability to potential final hosts of larval parasite taxa. A survey of the metazoan parasites of snoek (Thyrsites atun) caught in the Southern Benguela (n = 262) and the Northern Benguela (n = 87) revealed 18 taxa comprising 12 new geographic records for the Northern Benguela. A generalised additive mixed model (GAMM) indicated that infracommunity richness of snoek was determined by host size. Multivariate analyses revealed an ontogenetic shift, driven by an increase in the prevalence and infection intensity of trophically transmitted taxa (Anisakis sp., Corynosoma australe, Hepatoxylon trichiuri, Molicola uncinatus), in infracommunity structure as well as in the long-lived larval parasite assemblage. A ‗Random Forest‘ analysis selected Anisakis sp. and M. uncinatus as potential biological tags for assessing the population structure of snoek in the Benguela ecosystem. GAMMs with binomial and Tweedie error distributions were used to respectively assess the prevalence and abundance of both selected taxa in relation to host traits, seasonality and region of origin. The analyses demonstrated that anisakids were more prevalent and abundant in snoek caught in the Southern Benguela while M. uncinatus were more prevalent in snoek from the Northern Benguela. The spatial differences in infection levels of both parasite taxa suggest the presence of two snoek populations in the Benguela ecosystem. The information collected, collated and presented in this thesis has enabled an assessment of the present state of marine ichthyoparasitology off Southern Africa. Although the work uncovered a diverse ichthyoparasite fauna, it also revealed a bias towards particular parasitic taxa. The study highlighted a need for wide-ranging parasite surveys not restricted to certain host or parasite taxa in order to improve our knowledge of marine ichthyoparasite diversity in South Africa. The thesis also provided the first assessment of the drivers of parasite community assembly in the Southern Benguela and demonstrated that host ecology and the characteristics of the parasites played an important role in determining their distribution and interspecific distribution. Geographic differences in snoek parasite distribution patterns which reflect ecological variations across ecosystems have also proved useful to inform fishery management.